The use of artificial intelligence in health communication: A research on chatgpt - Tanyildizi, Nural Imik; Yildiz, Ilkay (IGI Global, 2024)
Communication is of great importance in health services. Nowadays, new media, especially the internet, are frequently used in health communication. Artificial intelligence has also begun to be used in healthcare. Artificial intelligence studies generally aim to develop artificial methods that imitate human ways of thinking. In addition, it is predicted that some programs produced based on artificial intelligence will affect health communication processes in daily use. The most important of these programs is the ChatGPT (Chatbot Generative Pre-trained Transformer) program. The purpose of this study is to reveal the benefits and drawbacks of using the ChatGPT program in health communication by providing a qualitative framework. For this purpose, a semi-structured interview was conducted with 30 people over the age of 18, determined by a purposeful sampling method. In line with the data obtained, the use of Chat GPT in health communication was tried to be explained. © 2024 by IGI Global. All rights reserved.